Membangunan Basis Metodologi Untuk Memperkokoh Keilmuan Fikih Berwawasan Keindonesiaan - Yusdani (Jurnal Hukum Islam, 2019)
Indonesian fiqh cannot be separated from the study of systems theory and the philosophy of science approach.Philosophy of science, with the target subject and object, is science (knowledge) includes two main topics,namely epistemology and methodology. To understand the text as a source of Islamic law, the discussion andapplication use macro interpretation, so that an understanding and interpretation of Islamic legal sourcesderived from the text of the Qur'an and Hadith is by the Indonesian context. The Indonesian context is thesubject and at the same Time the object of fiqh in discovering new laws in harmony with the legal needs ofIndonesian society. This condition is also an effort to strengthen Indonesia's fiqh position. Themethodological offer of Indonesian fiqh was carried out with a transdisciplinary approach, namely throughsystemic integration and interconnection, to discover the theory of truth in implementing Indonesian fiqh.The next problem is that fiqh as a science, cannot be released in a particular social and cultural context andcontains universal values that will always be relevant for each age and place following the objectives of fiqhitself and as a philosophy of Islamic law with the approach of system the maqasid based ijtihad.